The Effect Of The Use Of Online Geogebra Learning Media And Learning Style Categories On The Mathematical Communication Skills Of Junior High School Students - Syahidah, Alya Khansa; Miatun, Asih (Universitas Wiralodra, 2024)
This research aimed at testing, 1) whether there was a difference in mathematical communication skills of students in classes using Online GeoGebra and those not using Online GeoGebra; 2) whether there were differences in mathematical communication skills in terms of learning styles; 3) whether there was an interaction effect on students using Online GeoGebra and those not using Online GeoGebra and learning styles This research used a quasi-experimental design research method with a post-test only research design. The population of this research consisted of 8th-grade students with a total of 4 classes from of one of the Integrated Islamic Junior High Schools in Bekasi City. There were two groups for this research-the experimental group and the control group. The sample used consisted of two classes: one as The control class consisted 23 students and the other as the experimental class consisted 27 students. This research used two instruments: a questionnaire on learning styles and a test related to mathematical communication skills. Data analysis test using two-way ANOVA and Scheffe's multiple comparison test. The results of the research showed that, 1) there was a difference in mathematical communication abilities in classes using Online GeoGebra and those not using Online GeoGebra; 2) there were no differences in mathematical communication abilities in terms of learning styles; 3) there was an interaction between treatment and learning style on mathematical communication skills.